Impact of Globalization on Intercultural Communicative Competence and English Language Teaching in Nepal - Upadhyay, Mathura Prasad (KMC Journal, 2025)
This article explores how globalization restructures Intercultural Communicative Competence (ICC) with the growing use of English Language Teaching (ELT) in Nepal. With rapid globalization, the aim of language teaching has shifted from communicative competence to ICC. The objective of this study is to explore the impact of globalization on ICC and ELT by employing a qualitative literature review related to globalization utilizing secondary sources. With the rise of Westernization, it evaluates the inclusion of ICC in ELT curricula, suggesting strategies to balance local and global preserving their linguistic identity. It concludes that globalization has a long-term effect on Nepal’s socio-cultural dynamics which stresses the students to be proficient in ICC and ELT because English has become a global lingua franca and a carrier of culture as well. It also analyses the challenges and opportunities that have been brought about by globalization in ELT in Nepal. As Nepal is interconnected globally, it is significant to analyze how globalization redefines the English language learning and teaching process and how it is connected with the ICC of the learners. It further analyzes how globalization offers a more inclusive approach to language teaching which integrates cultural awareness into the curriculum. It concludes with curriculum reformation and teacher training by equipping the skills to navigate cultural plurality. Finally, it emphasizes to integrate ICC into ELT in developing global communicative skills, and promoting local cultural and linguistic traditions despite the risk of westernization and cultural homogenization in ELT in Nepal.